Analysis On Dimethyl Ether (Dme) Characteristics As A Liquid Petroleum Gas (Lpg) Fuel Substitution For Household Stove - Cahyo Setyo Wibowo; Riesta Anggarani; Dimitri Rulianto; Lies Aisyah (Scientific Contributions Oil and Gas, 2013)
Increasing growth of population will lead to increasing energy needs; therefore it is necessary to find alternative energy other than fossil fuel. Currently, energy sources in Indonesia are mainly derived from oil and natural gas such as LPG. Starting from 2008, LPG demand increased significantly for households and small industries as a result of government policy on conversion of kerosene to LPG. To meet this demand, the government imports LPG up to 2 million tons per year. In order to overcome LPG crisis, an alternative energy is required to be developed without changing either the distribution system, technical or commercial used. An option among others is dimethyl ether (DME) derived from low calori’s coal gasification. In this research analysis characteristics of DME is compared to LPG (as fuel reference) used. The test methods carried out refers to the specification of LPG issued by Directorate General of Oil and Gas. Based on the results, it shows that the characteristics of the fuel LPG mixed with DME 20% and 50% have some good results particularly on physical and chemical properties, stability and homogeneous of gas. Hence, LPG mixed DME 20% and 50% can be used as a substitute fuel for household stove.